Switch-on NIR probe for specific detection of Hg2+ ion in aqueous medium and in mitochondria - Agarwalla, Hrideshg; Mahajan, Pankaj S.; Sahu, Debashis; Taye, Nandaraj; Ganguly, Bishwajit; Mhaske, Santosh B.; Chattopadhyay, Samit; Das, Amitava (Inorganic Chemistry, 2016)
A new 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene (BODIPY)-based probe molecule (L) is synthesized for specific binding to Hg2+ ion in physiological condition with an associated luminescence ON response in the near-IR region of the spectrum. Appropriate functionalization in the 5-position of each of two pyrrole moieties with styryl functionality in a BODIPY core helped us in achieving the extended conjugation and a facile intramolecular charge transfer transition with a narrow energy gap for frontier orbitals. This accounted for a poor emission quantum yield for the probe molecule L. Binding to. Hg2+ helped in interrupting the facile intramolecular charge transfer (ICT) process that was initially operational for L. This resulted in a hypsochromic shift of absorption band and a turn-on luminescence response with lambda(Em)(max) of 650 nm on specific binding to Hg2+. Observed spectral changes are rationalized based on quantum chemical calculations. Interestingly, this reagent is found to be localized preferentially in the mitochondria of the live human colon cancer (Hct116) cells. Mitochondria is one of the major targets for localization of He2+, which actually decreases the mitochondrial membrane potential and modifies various proteins having sulfudryl functionality(ies) to cause cell apoptosis. Considering these, ability of the present reagent to specifically recognize Hg2+] in the mitochondrial region of the live Hct116 cells has significance.

Silver-mediated oxidative decarboxylative intramolecular asymmetric radical cyclization (C sp3 –C sp2 ) via memory of chirality: access to circumdatin alkaloids - Mahajan, Pankaj S.; Mhaske, Santosh B. (Organic Letters, 2018)
A novel silver-mediated oxidative decarboxylative intramolecular asymmetric radical cyclization has been developed to form a Csp3–Csp2 bond via memory of chirality. The application of the process has been demonstrated for the synthesis of the circumdatin class of alkaloids in high enantiopurity with retention of the configuration. The developed protocol is mild and works with an inexpensive silver catalyst in the absence of ligand, base, or additives. The involvement of a monoradical in the reaction has been established by trapping the radical intermediate.